Rift Valley Fever at Europe’s Risk Frontier: Climate, Vectors, and One Health Preparedness - Koycho Koev (Veterinary Sciences, 2026)
Background: Rift Valley fever (RVF) is a livestock-amplified, mosquito-borne zoonosis caused by Rift Valley fever virus (RVFV). Continental Europe has no established RVFV transmission, but a rare introduction could have major consequences if susceptible ruminants amplify infection before detection. Methodology: This critical narrative review synthesizes 69 scientific and institutional sources identified through structured PubMed/MEDLINE and Europe PMC searches, citation verification, and qualitative appraisal. Findings: European preparedness should distinguish probability from impact and weight evidence by decision value. Direct virological or acute animal evidence has the highest escalation value; serology, vector competence, environmental suitability, and pathway models mainly indicate where investigation should intensify. The main vulnerability is delayed recognition when animal movement or transported vector exposure coincides with seasonal receptivity and uneven surveillance capacity. Conclusions: The review develops a conditional convergence framework linking evidence strength to baseline vigilance, targeted investigation, and emergency response. Preparedness should prioritize differential diagnosis of livestock abortions and neonatal deaths, pathway-specific risk reduction, trigger-based sampling, occupational protection, and predefined vaccination and movement control decisions.